The Muslim Problem : Why We're Wrong About Islam and Why it Matters - Tawseef Khan (London Atlantic Books, 2021)
Why are Muslim men portrayed as inherently violent? Does the veil violate women's rights? Is Islam stopping Muslims from integrating? Across western societies, Muslims are perhaps more misunderstood than any other minority. How did we get here? In this landmark book, Tawseef Khan draws on history, memoir and original research to show what it is really like to live as a Muslim in the West. With unflinching honesty, he dismantles stereotypes from inside and outside the faith, and explores why many are so often wrong about even the most basic facts. Bold and provocative, Muslim, Actually is both a wake-up call for non-believers and a passionate new framework for Muslims to navigate a world that is often set against them.
Including Notes and Index
Keywords: Muslims -- Islam -- Great Britain